2019
DOI: 10.1016/j.apergo.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Pupillary measurement during an assembly task

Abstract: We conducted an empirical study of 57 children using a printed Booklet and a digital Tablet instruction for LEGO R construction while they wore a head-mounted gaze tracker. Booklets caused a particularly strong pupil dilation when encountered as the first media. Subjective responses confirmed the booklet to be more difficult to use. The children who were least productive and asked for assistance more often had a significantly different pupil pattern than the rest. Our findings suggest that it is possible to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, with the development of desktop-mounted eye trackers, pupil dilation and constriction can be measured non-invasively and remotely with high spatial and temporal resolution. In lab settings, where features such as luminance can be controlled and measured, recent work has shown success in using pupillometry to examine mental workload in an unconstrained setting (e.g., Lego construction; Bækgaard et al, 2019). In driving, some researchers have suggested that pupil-based measurements are highly relevant for assessment of drowsiness (Maccora et al, 2018).…”
Section: Research Applicability In Real-world Settingsmentioning
confidence: 99%
“…Moreover, with the development of desktop-mounted eye trackers, pupil dilation and constriction can be measured non-invasively and remotely with high spatial and temporal resolution. In lab settings, where features such as luminance can be controlled and measured, recent work has shown success in using pupillometry to examine mental workload in an unconstrained setting (e.g., Lego construction; Bækgaard et al, 2019). In driving, some researchers have suggested that pupil-based measurements are highly relevant for assessment of drowsiness (Maccora et al, 2018).…”
Section: Research Applicability In Real-world Settingsmentioning
confidence: 99%
“…Pupillometry, which refers to measuring pupil diameter, is one of the widely used physiological measures to assess cognitive load (Chen et al, ). Pupil dilation has been known for decades as a highly valid indicator of cognitive load (Bækgaard et al, ). Pupil dilation is known to occur up to 0.5 mm when performing mental effort tasks (Marquart & de Winter, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent advances in physiological measurements opened the possibility of doing this. Pupillometry, which refers to measuring pupil diameter, is one of the candidates for physiological measurement (Chen et al, ); pupil dilation has been known for decades as a highly valid indicator of cognitive load (Bækgaard, Jalaliniya, & Hansen, ). Hess and Polt () found that participants' pupil diameter differed as a function of difficulty during arithmetic tasks, leading the conclusion that pupil dilation was an index of total mental activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in eye-tracking technology enable pupil size measurement at various temporal rates 7,8) . Pupil dilation is modulated by the activity of the locus coeruleus in the noradrenergic system, and such pupillometry may offer new insights into dysautonomia in PD.…”
Section: Introductionmentioning
confidence: 99%